Self-oriented neural circuitry predicts other-oriented adaptive risks in adolescence: a longitudinal study. Issue 2 (25th June 2021) - Kwon, Seh-Joo; Turpyn, Caitlin C; Prinstein, Mitchell J; Lindquist, Kristen A; Telzer, Eva H
Abstract: Adolescence is marked by changes in decision-making and perspective-taking abilities. Although adolescents make more adaptive decisions with age, little is understood about how adolescents take adaptive risks that impact others and how this behavior changes developmentally. Functional coupling between reward [e.g., ventral striatum (VS)] and 'social brain' [e.g. temporal parietal junction (TPJ)/ posterior superior temporal sulcus (pSTS), medial prefrontal cortex (mPFC)] systems may be differentially shape adaptive risks for the self and other. A total of 173 participants completed between one and three sessions across three waves [a total of 433 behavioral and 403 functional magnetic resonance imaging (fMRI) data points]. During an fMRI scan, adolescents completed a risky decision-making task where they made risky decisions to win money for themselves and their parent. The risky decisions varied in their expected value (EV) of potential reward. Results show that from the 6th through 9th grades, adolescents took increasingly more adaptive risks for themselves than for their parent. Additionally, greater VS–TPJ/pSTS and VS–mPFC connectivity that tracks EV when making risky decisions for themselves in 6th grade, but a lower VS–mPFC connectivity in 9th grade, predicted greater adaptive risk-taking for their parent. This study contributes to our understanding of the self as a neural proxy for promoting adaptive social behaviors in youth.